The Effect Of Manager’s Bases Of Power On Employee’s Satisfaction With Supervision - See, Lee Pin (2014)
This study is to examine the relationship of the type of power bases used by managers upon employee’s job satisfaction, in particular on satisfaction with supervision. Power is a prevalent component in an organization and both managers and non managers use it extensively. Manager uses different power bases in dealing with their employees to achieve organizational goals and in a way, the employee’s perception towards the manager is influenced by that. For this study, French and Raven’s five dimensions of power bases were taken as the independent variables and their affect on employee’s satisfaction with supervision as the dependent variable.